Comment on 'Energy conservation and the constitutive relations in chiral and non-reciprocal media'. (22nd April 2016) - Mackay, Tom G; Lakhtakia, Akhlesh
Abstract: In a recent study (Barnett and Cameron 2016 J. Opt. 18 015404 ), in which energy conservation was considered in certain biisotropic mediums, the conclusions reached are inconsistent.